The impact of sleep-wake behaviour on tennis match performance in junior state grade tennis players - Turner, M.; Beranek, P.; Dunican, I. C.; Cruickshank, T. (Journal of Science in Sport and Exercise, 2023)
Purpose To date, no study has investigated the extent to which sleep-wake behaviour (SWB) influences match performance in junior tennis players. This study aimed to assess the influence of SWB for the week and night before on match performance, particularly match analytics and activity.